الإمام مسلم ومنهجه في صحيحه - Fatimah Ahmad; فاطمة بنت أحمد (Universiti Sains Islam Malaysia, 2022)
The purpose of this research is to study the profile of one of the hadith scholars that is ham Muslim Bin Hajjaj . It contains a brief introduction to his book " Sahih ", his writing method, the objective of writing and the number of hadith included. It also discusses the methodology used in writing the sahih The method used for gathering data in this study is mainly based on Iibrary research and revision of books related to the subject. It is found that Imam Muslim is considered as one of the famous hadith scholars and his book. Sahih is considered as the third in rank after Al-Quran and Sahih Bukhari. The book is written using distinct style and methods which is suitable and influence other scholars that come after him.